Influence of expiration date on analytical performance of rapid tests for HIV diagnosis - Feliciana L. O. Marinho; Nelson Luiz L. Santos; Suzane P. F. Neves; Leonardo S. Vasconcellos (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Introduction: Rapid tests (RTs) are ideal to provide laboratorial results within 30 minutes in a variety of situations and locations, even in underserved communities. Like any other laboratory input, they can only be used within the expiration date. Objective: The aim of this study was to compare the analytical performance of the RT Interkit HIV 1 and 2® (Interteck Katal - Belo Horizonte, Brazil) at two different times, two years before and one week before the expiration date. Material and methods: Two hundred serum samples were used, from individuals over 18 months of age, of both sexes, previously tested by electrochemiluminescence and Western Blot for HIV infection, distributed in two groups: reactive (n = 100) and non-reactive (n = 100). Results: The RT showed similar and satisfactory diagnostic accuracy in the two analyzed moments, with no statistical difference. Conclusion: The RT Interkit HIV 1 and 2® showed stable analytical performance both at the beginning and the end of its validity term.